Odpowiedzi

Najlepsza Odpowiedź!
2009-12-02T17:58:57+01:00
8a³+(b²+6):c= dla a=-1, b=-2, c=8

8*-1+(4+6):8= -8+10:8=6,25

4x-(5y²+8z³)= dla x=¼, y=0,2, z=-1

1-(0,1+(-1))=1-0,9=0,1



2.Oblicz:
a+(a+1,5)+2a+(a+3,5)= dla a=¾

0,75+2,25+1,5+0,75+3,5=8,75

12a= dla a=5,8

12a=69,6
2009-12-02T18:06:06+01:00
8* (-1) ³ + [(-2)² + 6 ]: 8 =
8 * -1 + ( 4 + 6 ) /8 =
-8 + 10/8 = -8 + 1 2/8 = -6 i3/4

4* 1/4 - [5(0,2)² + 8 (-1)³ ] =
1 - [ 5* 0,04 + 8 * (-1) ] =
1- 0,2 -8 = -7,2

3 (1/3)³+2[(1/3)²-3(2(1/3) -1)] =
3* 1/27 + 2[ 1/9 - 3( -8/9) =
1/9 + 2 ( 1/9 + 24/9)=
1/9 + 50/9 = 51/9 = 5 6/9 = 5 2/3